Performance Evaluation of Sharia Rural Banks: Maqashid Shariah Index Approach (Case Study: Sharia Rural Banks In West Java, Indonesia) - Tarmizi, Erwandi; Rachmad, Dedy; Ali, Zulkarnain Muhammad; Maulida, Syahdatul (PT Inovasi Pratama Internasional, 2024)
This study aims to measure the performance of Sharia Rural Banks in West Java using the maqashid sharia approach by Abdul Majid Najjar. The sample used in this study consists of 9 rural banks spread across West Java. The research data employed are secondary data in the form of financial reports for the year 2023 sourced from the Indonesia Financial Services Authority (OJK) website and governance reports for the year 2023 sourced from the official websites of each Sharia Rural Banks. The results of the study indicate that BPRS Al Salaam Amal Salman achieved the highest maqashid sharia score, followed by BPRS PNM Mentari and BPRS Almadinah Tasikmalaya Perseroda as the top three Sharia Rural Banks in West Java with the highest maqashid sharia index scores. Further analysis at the consequence level reveals that